2016
DOI: 10.2174/1568026615666150915121633
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Selenoprotein mRNA Tethering via Antisense Interactions with Ebola and HIV-1 mRNAs May Impact Host Selenium Biochemistry

Abstract: Regulation of protein expression by non-coding RNAs typically involves effects on mRNA degradation and/or ribosomal translation. The possibility of virus-host mRNA-mRNA antisense tethering interactions (ATI) as a gain-of-function strategy, via the capture of functional RNA motifs, has not been hitherto considered. We present evidence that ATIs may be exploited by certain RNA viruses in order to tether the mRNAs of host selenoproteins, potentially exploiting the proximity of a captured host selenocysteine inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 29 publications
5
58
2
Order By: Relevance
“…In addition to our published results showing antisense targeting of TR isoforms by HIV-1 and Ebola [13], and the current results for ZIKV, we have found that a number of other RNA viruses show potential antisense anti-TR interactions, including avian influenza and mumps virus; some of these are shown in Fig. S4 in the online Supplemental Materials.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In addition to our published results showing antisense targeting of TR isoforms by HIV-1 and Ebola [13], and the current results for ZIKV, we have found that a number of other RNA viruses show potential antisense anti-TR interactions, including avian influenza and mumps virus; some of these are shown in Fig. S4 in the online Supplemental Materials.…”
Section: Discussionsupporting
confidence: 77%
“…The results reported here suggesting that ZIKV virus (like several other pathogenic RNA viruses [13]), may engage in antisense interactions with the mRNA or pre-mRNA of isoforms of TR, a ubiquitous selenoprotein oxidoreductase, may provide a new explanation for the observed interactions between dietary selenium and the pathogenesis of viruses with RNA genomes. Antisense targeting of host TR isoforms leading to decreased TR protein levels could be an effective strategy for many RNA viruses.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations